Population-based preference weights for the Adult Social Care Outcomes Toolkit (ASCOT) for service users for Austria: Findings from a best-worst experiment. (April 2020) - Hajji, Assma; Trukeschitz, Birgit; Malley, Juliette; Batchelder, Laurie; Saloniki, Eirini; Linnosmaa, Ismo; Lu, Hui
Abstract: Background: The Adult Social Care Outcomes Toolkit (ASCOT) measures quality-of-life (QoL) outcomes of long-term care (LTC) service provision. Country-specific preference weights are required to calculate ASCOT scores. ASCOT has been translated into German, but lacks preference weights for German-speaking countries. Objectives: This paper aims to establish Austrian preference weights for the German version of the ASCOT service user measure, using best-worst scaling (BWS). Methods: Data were collected using an online BWS-experiment from a general population sample (n=1, 000) of Austrian adults. We use a scale-adjusted multinomial logit model (S-MNL) accounting for positioning effects to estimate preference weights. Results: Austrians value the top attribute-levels in the ASCOT domains 'being meaningfully occupied during the day' and 'having control over daily life' most highly, whereas high needs were the least preferred in the domains 'dignity' and 'social participation'. From a methods perspective, we found significant positioning effects only for 'best' choices, with statements at the top of a list being picked more often than those further down in the list. Factors related to survey completion (self-assessed understanding of the tasks and survey completion time) were shown to have the greatest effect on individual choice consistency. Discussion: The paper provides Austrian preference weights for the German version of ASCOT for service users. The weights also provide insight into how Austrians value different LTC-QoL states. Future research may investigate how values for different LTC-QoL states differ between socioeconomic groups. Highlights: Austrian preference weights for the ASCOT-Service User have been developed. Top levels in the domains 'occupation' and 'control' are valued the most. Bottom levels for 'dignity' and 'social participation' are valued the least. Positioning effects matter for 'best', but not for 'worst' choices. Factors related to survey completion have the greatest effect on choice consistency.